Development of novel composite antioxidant multiple lipid particles from combination of W/O/W multiple emulsions and solid lipid nanoparticles. Issue 7 (9th February 2015) - Zhao, Guodong; Hu, Caibiao; Sun, Rui; Ni, Shilei; Li, Qiwei; Xia, Qiang
<x xml:space="preserve">Abstract</x> A novel drug delivery system, multiple solid particles (MLPs), combining the advantages of water‐in‐oil‐in‐water (W/O/W) multiple emulsions and solid lipid nanoparticles (SLN) was proposed. The MLPs were produced by simply adding the solid lipid in liquid lipid of W/O/W multiple emulsions and removing the outer aqueous phase of W/O/W multiple emulsions. MLPs could form typical W/O/W multiple emulsion microstructure by self‐emulsifying after dispersing in water. MLPs were used to encapsulate both coenzyme Q10 and tea polyphenols (CT‐MLPs), and encapsulation efficiency measurement revealed that both coenzyme Q10 and tea polyphenols had high encapsulation efficiency (98.14% and 99.36%, respectively). The effect of the factors on viscosity, stability, and solubility of CT‐MLPs were investigated, and the results showed that increasing the concentration of solid lipid glycerin monostearate or hydrophilic emulsifier polyglyceryl‐10 laurate, or decreasing the concentration of the inner aqueous phase could increase the viscosity of CT‐MLPs. Consequently, the stability of CT‐MLPs was improved by increasing the viscosity of the oil phase. Moreover, addition of glycerin monostearate also increased the water solubility of CT‐MLPs. During a 60‐day stability study, CT‐MLPs showed terrific stability and high retention ratio (above 83.82%) at various conditions. Practical applications: MLPs could act as a drug delivery system to encapsulate both lipophilic active compounds and hydrophilic active compounds, since the active compounds in MLPs had high encapsulation efficiency. MLPs also improved the photostability and storage stability of coenzyme Q10 and tea polyphenols. Furthermore, the production procedure of MLPs is a two‐step stirring method, which is widespread and easy to handle. And the lipids for producing MLPs are physiological lipids, the choice of emulsifiers depends on the administration route. With regard to industrial production aspects, MLPs have the chance to be exploited as drug delivery system in commercial products. Hence, MLPs could be applicable delivery systems for food, cosmetic, and pharmaceutical applications.